KARAKTERISASI FISIKOKIMIA MINERAL LEMPUNG SEBAGAI BAHAN DASAR INDUSTRI KERAMIK DI DESA LEMBAH BOMBAN KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Siang Tandi Gonggo; Fina Edyanti; Suherman Suherman (Jurnal Akademika Kimia, 2013)
Clay is very important mineral in human life, especially as raw material for the fabrication of ceramics. Clay forms a mixture of minerals, which has a variety structure. The purity and type of mineral of clay as raw material determines the product quality of the resulting caramics. In this research, the type and structure of mineral has been characterized by XRD, XRF and SEM techniques and olso physical properties of the formation of clay ceramics have been axamined. The results of XRD characterization revealed that clay from Desa Lembah Bomban, Labuno, Parigi Motong regency contains kaolin, quartz, anorthit, cristobalite. Based on the results of XRF analysis, the clay contains SiO2 56.26%, Al2O3 23.18%, Fe2O3 4.99%, K2O 1.99%, MgO 1.73%, TiO2 0.980%, 0.841% Na2O ; CaO 0.840%. Physical characterization showed that from Desa Lembah Bomban clay was a less plastical type with linear drying shringkage of about 8.08%, linear firing shringkage 0.66% with total porisity of about 48.02%, and the compressive strength at 9000C about 8.135 x 106 (N/m2). SEM analysis results showed that the clay that has burned more dense than unfired.